Analisis Ujaran Kebencian Terhadap Fuji Utami Putri Dalam Kolom Komentar Postingan di Instagram Fuji Utami Putri - Christy Evelin; Grasella Ras Maria Br Damanik; Leni Fadia; Quratu Ainil Hilma (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The social media that is most often used and very liked by Indonesians is Instagram. This research focuses on comments from Indonesian netizens on the Instagram account of a public figure named Fuji, which is currently trending in Indonesia because her vlogs and uploads attract a lot of attention from Indonesian netizens. This research aims to describe hate speech carried out by netizens posted in the comments column of Fuji's Instagram posts. The development of information and communication technology has encouraged the emergence of language crime cases, for example incitement, blasphemy, threats, spreading fake news (hoaxes), bribery, conspiracy, perjury, defamation including slander and insults. This research uses a qualitative descriptive approach using literature review. The results of this research were to find and analyze 5 hate speeches in the comments column of Fuji's Instagram account posts. There are several tweets from netizens which are included in illocutionary speech acts containing hate speech towards the content creator named Fuji Utami Putri on social media.